1999
DOI: 10.1200/jco.1999.17.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitization With Carboplatin for Patients With Unresectable Stage III Non–Small-Cell Lung Cancer: A Phase III Trial of the Cancer and Leukemia Group B and the Eastern Cooperative Oncology Group

Abstract: Carboplatin at the dose and schedule used did not significantly impact on disease control or survival. The relapse rate within the chest remained more than 50%. More effective regimens will be required to impact on local disease control and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
1
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 210 publications
(91 citation statements)
references
References 22 publications
1
87
1
2
Order By: Relevance
“…The NSCLCCG meta-analysis confirmed the survival benefit provided by giving cisplatinbased chemotherapy before radiotherapy over radiotherapy alone (Non-Small Cell Lung Cancer Collaborative Group, 1995). Although it is standard to use induction chemotherapy followed by radiotherapy, there are some arguments favouring concurrent chemoradiation using chemotherapy at systemic dosages (Eberhardt et al, 1998;Jeremic et al, 1999) or at radiosensitising dosages (Trovo et al, 1992;Schaake-Koning et al, 1994;Bardet et al, 1997;Clamon et al, 1999). These two different treatment modalities have been studied in a number of promising phase II trials but there are very limited data from positive randomised phase III trials (Schaake-Koning et al, 1994;Furuse et al, 1999).…”
Section: Combined Modality and Adjuvant Therapymentioning
confidence: 99%
“…The NSCLCCG meta-analysis confirmed the survival benefit provided by giving cisplatinbased chemotherapy before radiotherapy over radiotherapy alone (Non-Small Cell Lung Cancer Collaborative Group, 1995). Although it is standard to use induction chemotherapy followed by radiotherapy, there are some arguments favouring concurrent chemoradiation using chemotherapy at systemic dosages (Eberhardt et al, 1998;Jeremic et al, 1999) or at radiosensitising dosages (Trovo et al, 1992;Schaake-Koning et al, 1994;Bardet et al, 1997;Clamon et al, 1999). These two different treatment modalities have been studied in a number of promising phase II trials but there are very limited data from positive randomised phase III trials (Schaake-Koning et al, 1994;Furuse et al, 1999).…”
Section: Combined Modality and Adjuvant Therapymentioning
confidence: 99%
“…Similar results were obtained for subgroup analysis of the five Phase-III trials. 15,19,20,21,37 Patterns of failure Pooling data of the initial relapse sites (Figure 2), difference between overall relapses (locoregional or distant) in both groups was statistically significant (OR ¼ 0.82; 95%CI: 0.69-0.97; p ¼ 0.02) in favor of concurrent group. Subset analyses revealed that isolated loco-regional relapses (primary tumor and/or regional nodes) were significantly lower frequent in the concurrent RT-CT than in the sequential arm (OR ¼ 0.68; 95%CI: 0.52-0.87; p ¼ 0.002), while the number of distant (e.g., brain, bone, or liver) relapses (OR ¼ 1.01; 95%CI: 0.79-1.30; p ¼ 0.927) and relapses at both sites (locoregional þ distant) (OR ¼ 0.74; 95%CI: 0.43-1.12; p ¼ 0.267) were similar in the two arms.…”
Section: Progression-free Survivalmentioning
confidence: 99%
“…For analyses of the survival, 33 patients (concurrent arm-16; sequential arm-17) had been excluded from the trial reported by Calmon et al 20 The main reason for exclusion was failure to meet eligibility criteria (e.g., weight loss more than the limit, incorrect clinical stage, and ineligible histology). Among the 10 trials, 3 trials showed a significant enhancement of survival for the concurrent RT-CT.…”
Section: Overall Survivalmentioning
confidence: 99%
See 2 more Smart Citations